Suicide ideation, planning, and attempts: the case of the LatinxLGB youth - Javier F. Boyas; Tatiana Villarreal-Otálora; Luis R. Alvarez-Hernandez; Mariam Fatehi (Tabriz University of Medical Sciences, 2019)
Background: Guided by an ecological systems theory (EST) framework, the purpose of the present study was to investigate how multiple micro, mezzo, and macro factors influence the suicidality continuum from suicidal ideation to suicide attempt among Latinx LGB (lesbian, gay, and bisexual) youth living in the United States. Methods: Data for this cross sectional-study included 451 participants who self-identified as Latinx LGB on the 2017-National Youth Risk Behavioral Survey. The analysis explored micro, mezzo, and macro-level factors' association with three suicidality outcomes (ideation, planning, and attempt) at the bivariate and multivariate level. Since the outcome variables were dichotomized, univariate logistic regressions and backward elimination logistic regressions were used. Results: The most commonly reported suicidal behavior was ideation (n = 173; 40%), followed by planning (n = 150; 34%), and then attempt (n = 64; 21%). Findings from the backward elimination logistic regression on suicidal ideation suggest the best set of independent variables are being bullied at school (odds ratio [OR] = 2.81; CI: 1.61-4.89), experiencing sexual assault(OR = 2.32; CI: 1.32-4.07), experiencing depressive symptoms (OR = 1.99; CI: 1.07- 3.69),being cannabis use (OR = 1.76; CI: 1.08-2.89), and being female (OR = 1.72; CI: 1.01-2.93).For suicide planning the model suggested, experiencing depressive symptoms (OR = 3.21; CI:1.74-5.91), cannabis use (OR = 2.46; CI: 1.49-4.07), being bullied at school (OR = 2.04; CI:1.17-3.58), and experiencing sexual assault (OR = 1.88; CI: 1.07-3.31) exhibited the strongest relationships. Suicide attempt was significantly associated with cannabis use (OR = 3.12; CI:1.60-6.08), experiencing depression (OR= 2.89; CI: 1.30-6.43), experiencing sexual assault(OR = 2.77; CI: 1.34-5.71), and being bullied at school (OR = 2.34; CI: 1.12-4.91). Conclusion: Given the findings of this study, it is essential that tailored suicide prevention efforts be established that uniquely address the intersections of race/ethnicity and sexual orientation and how this intersection influences micro, mezzo, and macro factors associated with suicide ideation, planning, and attempt among Latinx LGB adolescents.